2021
DOI: 10.1186/s12884-021-03977-1
|View full text |Cite
|
Sign up to set email alerts
|

The hidden burden of adolescent pregnancies in rural Sri Lanka; findings of the Rajarata Pregnancy Cohort

Abstract: Background Adolescent fertility is a main indicator of the Sustainable Developmental Goal (SGD) three. Although Sri Lanka is exemplary in maternal health, the utilization of Sexual and Reproductive Health services (SRH) by adolescents is less documented. We describe the hidden burden, associated biological and psychosocial factors and utilization patterns of pre-conceptional services among pregnant adolescents in rural Sri Lanka. Methods The study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Apart from a Nepalese context, a case-control study from Sri Lanka [ 28 ] also found that women from a Tamil ethnic background were more prone to adolescent pregnancy compared to those of non-Tamil ethnicity. A cohort study from Sri Lanka [ 15 ] revealed that lower contraceptives use was significantly associated with adolescent pregnancy; in contrast, a cross-sectional study from Bangladesh [ 18 ] found that women who used contraceptives were more predisposed to adolescent pregnancy as compared to those who never used contraceptives. Studies in Nepal [ 11 ] and Bangladesh [ 19 , 21 ] found a higher level of adolescent pregnancies among girls with no access to mass media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from a Nepalese context, a case-control study from Sri Lanka [ 28 ] also found that women from a Tamil ethnic background were more prone to adolescent pregnancy compared to those of non-Tamil ethnicity. A cohort study from Sri Lanka [ 15 ] revealed that lower contraceptives use was significantly associated with adolescent pregnancy; in contrast, a cross-sectional study from Bangladesh [ 18 ] found that women who used contraceptives were more predisposed to adolescent pregnancy as compared to those who never used contraceptives. Studies in Nepal [ 11 ] and Bangladesh [ 19 , 21 ] found a higher level of adolescent pregnancies among girls with no access to mass media.…”
Section: Resultsmentioning
confidence: 99%
“…There have been individual studies reporting the burden and factors associated with adolescent pregnancy in various countries within South Asia [ 11 , 12 , 14 , 15 ]. These individual studies differ in design and methodology, thus making it difficult to make informed intra-regional comparisons and roll out effective initiatives to substantially reduce adolescent pregnancy within the region.…”
Section: Introductionmentioning
confidence: 99%
“…Four other studies qualified this finding, arguing that previous experience with health workers strongly influences future maternal health care seeking behaviour [ 14 , 21 , 22 ]. Low levels of maternal and paternal education and unmarried mothers are some factors that can lead to discrimination and disrespect in rural settings, and these are significant factors that have been associated with adolescent pregnancy in a study conducted in Sri Lanka [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A baixa escolaridade tem sido fortemente relacionada à gravidez na adolescência, em que muitas adolescentes não frequentam ou desistem da escola em decorrência da gravidez (7,9,(18)(19)(20) . A preocupação em torno disso recai nas consequências futuras que a pouca escolaridade e o baixo nível educacional poderão gerar nas condições socioeconômicas, como menor emprego e renda, bem como limitado acesso à informação e a cuidados de saúde de qualidade, impactando negativamente no crescimento e desenvolvimento infantil.…”
Section: Discussionunclassified